Effective Teaching Strategies to Enhance Critical Thinking Skills in Education: A Literature Review - Darminto, Darminto; Handoyo, Eko; Wardani, Sri; Subali, Bambang; Widiarti, Nuni (research, training and philanthropy institution Natural Aceh, 2025)
Critical thinking skills are essential in modern education and are important in sound decision-making and problem-solving. Therefore, effective teaching in developing students' critical thinking skills must be taken seriously. This article aims to review various effective teaching strategies in improving critical thinking skills at different levels of education. This research uses a literature study approach by analyzing recent articles discussing teaching methods, focusing on developing critical thinking. Based on the literature review conducted, it was found that methods such as Problem-Based Learning (PBL) and inquiry-based learning (IBL) proved to be very effective in improving critical thinking skills. PBL, which encourages students to solve real problems in groups, provides hands-on experience in critical thinking. In addition, IBL teaches students to ask questions and explore answers independently and actively. Both methods improve students' analytical and evaluative skills at primary and tertiary education levels. However, challenges in implementation include the need for ongoing training for educators and limited resources. In conclusion, teaching based on these methods effectively improves students' critical thinking skills and prepares them to face the challenges of the complex world of work.